2015
DOI: 10.1002/path.4634
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic pathophysiology in cystic fibrosis

Abstract: The pancreas is one of the earliest- and most commonly- affected organs in patients with cystic fibrosis (CF). Studying the pathogenesis of pancreatic disease is limited in CF patients due to its early clinical onset, co-morbidities and lack of tissue samples from early phases of disease. In recent years, several new CF animal models have been developed that have advanced our understanding of both CF exocrine and endocrine pancreatic disease. Additionally, these models have helped us better define the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 110 publications
(189 reference statements)
1
97
0
8
Order By: Relevance
“…They showed that the site of obstruction ranged from the distal jejunum to the proximal spiral colon, similar to that reported in humans with meconium ileus (59,63). The obstruction in the acini and ducts lead to dilatation which causes epithelial injury and destruction, inflammation, fibrosis and fatty infiltration (30,41,59). Tucker and colleagues reported that acinar plugs developed before mucous metaplasia and found that early acinar plugs are composed of zymogen granules and were distinct from mucus in pancreatic tissue of cystic fibrosis patients (104).…”
Section: Cftr Function and Its Role In Pancreas Cystic Fibrosis And Esupporting
confidence: 56%
See 3 more Smart Citations
“…They showed that the site of obstruction ranged from the distal jejunum to the proximal spiral colon, similar to that reported in humans with meconium ileus (59,63). The obstruction in the acini and ducts lead to dilatation which causes epithelial injury and destruction, inflammation, fibrosis and fatty infiltration (30,41,59). Tucker and colleagues reported that acinar plugs developed before mucous metaplasia and found that early acinar plugs are composed of zymogen granules and were distinct from mucus in pancreatic tissue of cystic fibrosis patients (104).…”
Section: Cftr Function and Its Role In Pancreas Cystic Fibrosis And Esupporting
confidence: 56%
“…In addition, MUC6 mucin is the main constituent of the complexes that form in small ducts and cause obstruction (81). Therefore, CF patients carrying mutations in the CFTR gene, showed a lower pH, low flow of secretions and high protein concentration in the pancreas duct secretions, which lead to precipitates in the duct lumina that obstruction and injury (30,117). Meyerholz and his colleagues showed in the CF pig model that the changes (obstruction) could be detected in gestations as early as week 17 (59).…”
Section: Cftr Function and Its Role In Pancreas Cystic Fibrosis And Ementioning
confidence: 99%
See 2 more Smart Citations
“…Die Folge ist ein progredienter absoluter Insulinmangel, welcher sich in einem Cystic Fibrosis-related Diabetes Mellitus (CFRD) äußert [35]. Die Symptomatik des CFRD potenziert sich durch den gesteigerten Energiebedarf von MukoviszidosePatienten im Rahmen der Malabsorption sowie der rezidivierenden Atemwegsinfektionen.…”
Section: Genetik Der Mukoviszidoseunclassified